Pemodelan dan Analisa Pembangkit Listrik Tenaga Microhydro Menggunakan Turbin Crossflow - Negoro, Andra Cahyo; Prabowo, Yuliyanto Agung (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
The use of water as a natural resource and renewable energy for electricity generation is an alternative solution to replace fossil fuels, whose availability is becoming increasingly scarce. The water flow in Embung Tambong, Bangunsari Hamlet, Pule District, Trenggalek Regency, East Java, became a research location for designing micro-hydro power plants (MHPP). Before designing a micro-hydro power plant, a potential study was carried out to get a general idea of the potential magnitude of the water-energy production. The results of field observations and research through a water flow sensor obtained the highest water discharge at 0.1412 m3/second. Meanwhile, the measurements obtained an effective waterfall height (heff) of 5.69 meters. The data on water discharge and effective fall height were employed to plan a crossflow-type turbine as a driver for the micro-hydro power generator. The simulation of a micro-hydro power plant using MATLAB Simulink by adding a lead-lag compensator controller to the micro-hydro power plant system produced a fast system response and obtained a low steady-state error value. Using the maximum water discharge data, the potential for electrical energy generated from a micro-hydro power plant was 5105.90 watts.